DICOMStudio: plataforma multidomínio para a telerradiologia - Lucena Neto, Juracy Regis de (2018)
For diagnostic purposes, teleradiology allows medical imaging exams be retrieved and transmitted remotely. However, the teleradiology workflow integration has technological and social issues which makes a creation of a common communication platform between entities and physicians difficult. Objective: To propose a multidomain, opened, asynchronous and flexible platform for a teleradiology, called DICOMStudio. Method: An architectural model based on DICOMFlow was designed and an application was developed for transmission of reports by physicians and information control by the clinic. Results: Preliminary tests are being carried out to evaluate the technical and operational feasibility of the platform. The tests take place with the help of a radiologist and a real clinic. Conclusion: DICOMStudio provides the teleradiology workflow integration which includes radiologists and medical clinics, solving a bunch of technical and social limitations.